(a+b) (b+c) (a+c) 28abc, если а > 0, b>0 и с 0; (ab +1)(a+b) = 4ab, если а>0 и b = 0;

Лера12435 Лера12435    2   17.09.2021 20:38    0

Ответы
FubZ1k FubZ1k  17.09.2021 20:40

ответ: Раскроем скобки:

(a+b)*(b+c)*(c+a)=2abc+ab^2+ac^2+ba^2+bc^2+ca^2+cb^2

Преобразуем:

(a+b)*(b+c)*(c+a)=a(b^2+c^2)+b(a^2+c^2)+c(a^2+b^2)

Так как 8abc=2abc+6abc, то достаточно доказать, что:

6abc <= a(b^2+c^2)+b(a^2+c^2)+c(a^2+b^2)

Очевидно, 2xy <= x^2+y^2, так как (x-y)^2 >= 0.

Значит, 2abc <= a(b^2+c^2), 2abc <= b(a^2+c^2), 2abc <= c(a^2+b^2)

Складываем эти неравенства и получаем:

6abc <= a(b^2+c^2)+b(a^2+c^2)+c(a^2+b^2)

Неравенство доказано.

Объяснение: ...

ПОКАЗАТЬ ОТВЕТЫ